2022
DOI: 10.1161/hypertensionaha.121.18809
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances and Incident Hypertension in Multi-Racial/Ethnic Women: The Study of Women's Health Across the Nation

Abstract: Background: Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are ubiquitous synthetic chemicals that may disrupt blood pressure controls; however, human evidence to support this hypothesis is scant. We examined the association between serum concentrations of PFAS and risks of developing hypertension. Methods: This study included 1058 midlife women initially free of hypertension from the multiracial and multiethnic SWAN (Study of Women’s Health Acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 73 publications
(119 reference statements)
3
25
0
Order By: Relevance
“…Immune system (a) Reduced formation of vaccine antibodies [182,183,191,192,485,486] (b) Autoimmune diseases: Colitis ulcerosa [487] 10. Heart, circulatory system Cardiovascular issues [488][489][490][491][492] Hypertension [410,488,493,494] 11. Genetics: epigenetic PFAS-effects can be transferred to following generations [455,[495][496][497][498][499] 12.…”
Section: Affected Organ/function Consequencesmentioning
confidence: 99%
“…Immune system (a) Reduced formation of vaccine antibodies [182,183,191,192,485,486] (b) Autoimmune diseases: Colitis ulcerosa [487] 10. Heart, circulatory system Cardiovascular issues [488][489][490][491][492] Hypertension [410,488,493,494] 11. Genetics: epigenetic PFAS-effects can be transferred to following generations [455,[495][496][497][498][499] 12.…”
Section: Affected Organ/function Consequencesmentioning
confidence: 99%
“…Analysis of participants in the SWAN study (females only, United States, 1281 participants) showed that both PFOA and PFOS were strongly associated with increased risk of hypertension. 88 In contrast, studies of populations with both genders and larger age ranges did not show longitudinal associations between PFAS body burden and the risk of hypertension. Participants in the DPP study (United States, 957 participants) showed null associations between PFOA, PFNA, PFHxS, or PFOS with the risk of hypertension.…”
Section: Pfas and Cvd Risk Factorsmentioning
confidence: 93%
“…90,91 Data from the National Health and Nutrition Examination Survey demonstrate the ubiquity of per- and polyfluoroalkyl substance exposure. 92 Due to their structural similarity to fatty acids, per- and polyfluoroalkyl substances may interfere with the action of peroxisome proliferator-activated receptors and their signaling pathways. Recent evidence suggests strong evidence linking a variety of per- and polyfluoroalkyl substances with cardiovascular outcomes, including hypertension.…”
Section: Urban Provisioning Systems and Exposures Affecting Human Healthmentioning
confidence: 99%
“…Recent evidence suggests strong evidence linking a variety of per- and polyfluoroalkyl substances with cardiovascular outcomes, including hypertension. 92 Most urban water management systems in the United States do not purify chemicals and metals and, thus, these concerns demand the transformation of urban water systems from source to use.…”
Section: Urban Provisioning Systems and Exposures Affecting Human Healthmentioning
confidence: 99%